Multilingual Education Yearbook 2018 Internationalization, Stakeholders & Multilingual Education Contexts (Multilingual Education Yearbook,, 2018)
This volume examines how internationalization, stakeholders, and educational contexts have a reciprocal influence on multilinguals and their communities both as individual and collective variables. Therefore, the exploration of these variables and how they intersect and interact with worldwide phenomena like globalization, global citizenship, and responsive and responsible provisions of education are the central foci of this volume. Contributors from different parts of the world draw on analyses of various forms of data to foreground these foci with implications for effective multilingual education practices in their contexts, and beyond. The Multilingual Education Yearbook publishes high-quality empirical research on education in multilingual societies. It publishes research findings that, in addition to providing descriptions of language learning, development and use in language contact and multilingual contexts, will shape language education policy and practices in multilingual societies.